1998
DOI: 10.1021/ic980324c
|View full text |Cite
|
Sign up to set email alerts
|

Forbidden Electronic Transitions between the Singlet Ground State and the Triplet Excited State of Pt(II) Complexes

Abstract: Direct access to the triplet emitting state from the ground state is observed for Pt(II) complexes containing heterocyclic (CwedgeC', CwedgeN, NwedgeN') and bis(diphenylphosphino)alkane (PwedgeP') ligands. Extinction coefficients for such transitions are in the range 4-25 M(-)(1) cm(-)(1). Emission quantum yields resulting from singlet-to-triplet excitation are as high as 61-77 times the emission quantum yields resulting from singlet-to-singlet excitation at 296 K. The intersystem crossing quantum yield from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 12 publications
3
18
0
Order By: Relevance
“…This implies that prior phosphine dissociation from [Pt(2,2 -bph)(PEt 3 ) 2 ] (44) is not a prerequisite for H 2 addition. The reductive elimination of biphenyl from trans-[PtH(␣-bph)(PEt 3 ) 2 ] was inhibited by added phosphine.…”
Section: Catalysis By Metal 22 -Biphenyl Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…This implies that prior phosphine dissociation from [Pt(2,2 -bph)(PEt 3 ) 2 ] (44) is not a prerequisite for H 2 addition. The reductive elimination of biphenyl from trans-[PtH(␣-bph)(PEt 3 ) 2 ] was inhibited by added phosphine.…”
Section: Catalysis By Metal 22 -Biphenyl Complexesmentioning
confidence: 99%
“…the now popular 2-phenylpyridine complexes mentioned in the Introduction [3,4]. Rillema and co-workers have extensively studied the absorption and emission properties of a number of Pt(2,2 -bph) complexes with the mono-and bidentate ligands, pyridine, acetonitrile, ethylenediamine, CO (27) [23,42], dppm [44,45], and the bridging ligand SEt 2 [41]. Absorption spectra of mono-metallic [Pt(2,2 -bph)(py) 2 ] (52), [Pt(2,2 -bph)(NCMe) 2 ] bonyl complex 27 have been carried out to examine singlet and triplet excited states, and to compare calculated geometries with those from the X-ray crystallographic data previously obtained [42,43].…”
Section: Luminescent Transition Metal 22 -Biphenyl Complexesmentioning
confidence: 99%
“…The complex 1 with bzq ligand shows longer lifetime as compared to that for the complex 2 with ppy ligand, which may be due to a predominant 3 IL contribution in complex 1 26,43. This behavior has been assigned to the existence of a lesser excited-state, singlet-triplet splitting in the complex 1 leading to a higher intersystem crossing quantum yield 50 and longer lifetime 26,27,31,51. Complex 2 shows a higher luminescence quantum efficiency compare to complex 1, which may be related to difference of radiative decay rate (k r ) in these complexes (seeTable 2) 43.…”
mentioning
confidence: 92%
“…94À96 This fact has been attributed to the occurrence of a smaller excited-state, singletÀtriplet splitting in the bzq compounds, which leads to higher intersystem crossing quantum yield and longer lifetimes. 95,96 All complexes are emissive in fluid solution and in the glass state. Taking into account that 7 and 8 are only soluble in CH 3 CN, this solvent was chosen for the comparative photophysical study of all of the derivatives (shown in Table 1).…”
Section: ' Introductionmentioning
confidence: 99%